Scientific Realism in the English for Nursing Course Plan: A Content Analysis - Suci Sartika Putri; Ira Maisarah (Universitas Pahlawan Tuanku Tambusai, 2026)
English for Specific Purposes (ESP) emphasizes the importance of designing language instruction that reflects authentic professional practices and workplace demands. Aligning course plans with real-world contexts is therefore essential to ensure that learning outcomes are meaningful and applicable. This study aimed to examine how the principles of scientific realism are represented in an English for Nursing course plan used at a health college in Bengkulu City. A qualitative content analysis approach was employed to analyze the course plan through three stages: document collection, pre-analysis, and systematic coding. The data were organized according to three core principles of scientific realism: causal mechanisms, approximate truth, and explanatory success. The findings revealed that the learning outcomes reflected the principle of causal mechanisms by emphasizing logical relationships between language use and nursing practice. The instructional materials represented approximate truth through authentic professional content, while the assessment components demonstrated explanatory success by evaluating students’ ability to apply language in realistic nursing contexts. Overall, the study concludes that integrating scientific realism into ESP course planning enhances the relevance, authenticity, and practical value of English for Nursing instruction.